Progress in implementation of the WHO FCTC Article 14 for tobacco dependence treatment internationally - Nilan, Kapka (2019)
Tobacco use is the leading cause of preventable disease, disability and premature death globally. While tobacco consumption has decreased in many high income countries, demand for tobacco continues to grow in many low and middle income countries. Offering tobacco users help to stop using tobacco is a key demand reduction measure outlined under Article 14 of the World Health Organisation (WHO) Framework Convention on Tobacco Control (FCTC) a global public health treaty ratified by 180 countries and covering almost 90% of the world's population. The main aim of this thesis was to assess progress in implementation of FCTC Article 14 and its guidelines globally and explore the association between implementation and country income level, focussing on tobacco treatment guidelines development, tobacco dependence treatment provision, and tobacco use among healthcare workers (HCWs).